Agraphs: Definition, implementation and tools - Déharbe, David; Moreira, Anamaria; Sena, Demóstenes (Electronic Communications of the EASST, 2007)
Agraphs are a graph-based language representation, transformation and exchange format. In the same vein as XML, Agraphs form a general data representation mechanism that needs to be instantiated in different specific applications. In this paper, we present the Agraphs data structure, programming interface and related tools, identify their main features with respect to exchange format characteristics, and compare them to other existing exchange formats. These different features are illustrated on an instance of Agraphs for modular Petri nets.